2013
DOI: 10.1116/1.4774326
|View full text |Cite
|
Sign up to set email alerts
|

Structural, surface, and thermomechanical properties of intrinsic and argon implanted tetrahedral amorphous carbon

Abstract: The structural, surface, and thermomechanical properties of intrinsic and argon incorporated tetrahedral amorphous carbon films deposited using the filtered cathodic vacuum arc process are reported. Argon atoms were simultaneously incorporated during the deposition of the films using an argon ion gun in the energy range of 0–180 eV. Contact angle measurements revealed that all of the deposited films are hydrophobic, regardless of the substrate bias voltage that was applied during the depositions. Thermal desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Ion beam deposition, Mass-selected ion beam deposition (MSIB), and filtered arc cathode deposition (FCVA) have been used to deposit hydrogen free DLC films [16][17][18][19]. Z. Tang et al [16] have been investigated DLC films deposited using the MSIB method and observed that the DLC films with high optical band gap, low surface roughness and high thermal stability obtained through mass-selected carbon ions species with ion energy of 100 eV.…”
Section: Introductionmentioning
confidence: 98%
“…Ion beam deposition, Mass-selected ion beam deposition (MSIB), and filtered arc cathode deposition (FCVA) have been used to deposit hydrogen free DLC films [16][17][18][19]. Z. Tang et al [16] have been investigated DLC films deposited using the MSIB method and observed that the DLC films with high optical band gap, low surface roughness and high thermal stability obtained through mass-selected carbon ions species with ion energy of 100 eV.…”
Section: Introductionmentioning
confidence: 98%
“…1, [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][87][88][89][90] The D band is a breathing mode of A 1g symmetry, and its intensity is strictly related to the occurrence of six-fold aromatic rings in the scattering medium. Table I) which reduces aromatic ring formation.…”
Section: Visible Raman and Pl Spectroscopies: Sp 2 Clusteringmentioning
confidence: 99%
“…By correct interpretation of the different parameters derived from the spectral analysis from curve fitting of MW Raman 35,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] and PL 38-40,69-73 spectra, we report that it is possible to distinguish between DLC:H films with minute differences in bonding configuration, microstructure, and hydrogen content and to follow their thermally induced structural evolution. Most importantly, we introduce a new analysis method of Raman spectra that permits distinguishing between films prepared with different density, thickness, and RTA treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "knock-on" process transforms sp 2 into sp 3 bonds, which is responsible for the increase in the compressive stress of the films [13,[18][19][20]. For energies above 100 eV, the stress reaches a limit with a subtle decrease trend towards higher energy due to the "thermal spike" effect, which promotes a distortion in the carbon matrix creating defects and consequent relaxation of the network.…”
Section: Resultsmentioning
confidence: 99%